The quantitative impact of COVID-19 on surgical training in the United Kingdom. Issue 3 (25th June 2021) - Clements, J M; Burke, J R; Hope, C; Nally, D M; Doleman, B; Giwa, L; Griffiths, G; Lund, J N
Abstract: Background: COVID-19 has had a global impact on all aspects of healthcare including surgical training. This study aimed to quantify the impact of COVID-19 on operative case numbers recorded by surgeons in training, and annual review of competency progression (ARCP) outcomes in the UK. Methods: Anonymized operative logbook numbers were collated from electronic logbook and ARCP outcome data from the Intercollegiate Surgical Curriculum Programme database for trainees in the 10 surgical specialty training specialties. Operative logbook numbers and awarded ARCP outcomes were compared between predefined dates. Effect sizes are reported as incident rate ratios (IRR) with 95 per cent confidence intervals. Results: Some 5599 surgical trainees in 2019, and 5310 in surgical specialty training in 2020 were included. The IRR was reduced across all specialties as a result of the COVID-19 pandemic (0.62; 95 per cent c.i. 0.60 to 0.64). Elective surgery (0.53; 95 per cent c.i. 0.50 to 0.56) was affected more than emergency surgery (0.85; 95 per cent c.i. 0.84 to 0.87). Regional variation indicating reduced operative activity was demonstrated across all specialties. More than 1 in 8 trainees in the final year of training have had their training extended and more than a quarter of trainees entering their final year of training are behind their expected training trajectory. Conclusion: The COVID-19 pandemic has had a major effect on surgical training in the UK. Urgent, coordinated action is required to minimize the impacts from the reduction in training in 2020. Abstract : This study reports the impact of the COVID-19 pandemic on operative surgical training in the United Kingdom, demonstrating significant reduction in operative training, especially in elective procedures, across the UK, and a consequent impact on trainee progression, as measured by ARCP outcome.